Determinan Cash Holding Perusahaan Sub Industri Perkebunan dan Tanaman Pangan di Indonesia - Zaidah Rizkiyah; Darto Darto (Masyarakat Ekonomi Syariah Bogor, 2026)
The plantation and food crop sector plays and important role in the Indonesian economy, but this industry faces the risk of price fluctuations and operational instability, which requires companies to maintain liquidity through optimal cash holding policies. This study aims to analyze the effect of Current Ratio (CR), Debt to Equity Ratio (DER), Return on Asset (ROA), and Firm Size on Cash Holding in plantation and food crop sub-industry companies listed on Indonesia Stock Exchange during the periode 2020-2024. The research method use a quantitative approach with panel data regression analysis and a sample selection of 20 companies through purposive sampling. The result of this study indicate that CR, DER, and Firm Size have a positive but insignificant effect on Cash Holdings, while ROA has a positive and significant effect on Cash Holdings. An R2 value of 0.7745 indicates that the independent variables are able to explain 77,45% of Cash Holding. These findings imply that profitability is a major factor that strengthens a company’s ability to maintain cash, so management needs to optimize asset performance. In addition, the results of this study can be taken into consideration by investors in assessing the financial stability of companies and a reference for further research.